A brief exposure to toluene vapor alters the intrinsic excitability of D2 medium spiny neurons in the rat ventral striatum - Okas, Michael; Kastner, Abigail; Gioia, Dominic; Woodward, John J. (Frontiers in Neuroscience, 2023)
Although volatile organic solvents such as toluene are used for commercial and industrial uses, they are often voluntarily inhaled for their intoxicating and euphoric effects. Research into the effects of inhalants such as toluene on brain function have revealed actions on a variety of ligand-gated and voltage-activated ion channels involved in regulating neuronal excitability. Previous work from this laboratory has also shown that brief exposures to toluene vapor induce changes in the intrinsic excitability and synaptic transmission of neurons within the medial prefrontal cortex and ventral tegmental area that vary depending on projection target. In the present study, we recorded current-evoked spiking of medium spiny neurons (MSNs) in the nucleus accumbens (NAc) core and shell in adolescent rats exposed to an intoxicating concentration of toluene vapor. Compared to air controls, firing of NAc core MSNs in Sprague-Dawley rats was not altered 24h after exposure to 10,500 ppm toluene vapor while spiking of NAc shell MSNs was enhanced at low current steps but reduced at higher current steps. When the rheobase current was used to putatively identify MSN subtypes, both "D1-like" and "D2-like" MSNs within the NAc shell but not core showed toluene-induced changes in firing. As toluene may itself have altered the rheobase resulting in misclassification of neuron subtype, we conducted additional studies using adolescent D2-Cre rats infused with a Cre-dependent mCherry reporter virus. Following toluene vapor exposure, spiking of NAc shell D2+ MSNs was enhanced at low current steps but inhibited at higher currents as compared to air controls while there were no differences in the firing of NAc shell D2-MSNs.The toluene-induced change in NAc D2+ shell MSN firing was accompanied by alterations in membrane resistance, rheobase, action potential rise time and height with no changes noted in D2-MSNs. Overall, these data add to a growing literature showing that brief exposures to intoxicating concentrations of toluene vapor causes selective alterations in the excitability of neurons within the addiction neurocircuitry that vary depending on sub-region, cell-type and projection target.